O projeto público de colonização mista no planalto rio-grandense: as Colônias Erechim (1908) e Santa Rosa (1915) - Schmitz, Kalinka de Oliveira (Universidade do Vale do Rio dos Sinos, 2024)
During the First Republic, the immigration and colonization process that had been underway in Rio Grande do Sul for almost a century underwent new changes. At a time when several legislative and governmental changes were made to adapt to the objectives and interests of this new political period, the issue of land and colonization also received attention at the state and federal levels. In Rio Grande do Sul, concerns about how to manage the still vacant lands, where their finiteness was envisioned, as well as a concern about the insertion of the colonial population into Rio Grande do Sul's society and economy, were present in legislative discussions and the projects put into practice by government bodies. Responsible for the public colonial nuclei created during the Empire, the PRR government, through the Directorate of Lands and Colonization, began both to administer them and to design colonial projects of its own, both to meet the strong demand for new colonial spaces and also so that they could be carried out in the way they saw fit. It was in this context that the Erechim Colony was created in 1908, in the municipality of Passo Fundo, and in 1915 the Santa Rosa Colony was created in the municipality of Santo Ângelo; the main public colonial centers in the 20th century had the heterogeneous character of the previous public enterprises - Ijuí and Guarani mainly - expanded, each with its particularities in its conformation and development. While in the Erechim Colony, the mixed character is seen mainly in the ethnic diversity of immigrants and their descendants from the old colonies, in Santa Rosa the group classified by the government as nationals made up the majority of the population, largely due to the creation of the Nationals Protection Service (later expanded to Erechim). That said, the aim of this thesis, using Comparative History, is to analyze and discuss these mixed public colonial projects in Erechim and Santa Rosa, from the context and discussions that preceded the act of creation, the administrations of each nucleus, the way in which the mixed character was implemented in each and the possible conflicts that emerged from these rural spaces and diverse ethnic composition.
Keywords: Colonização mista; Colônia Erechim; Colônia Santa Rosa; Rio Grande do Sul; Primeira República; Mixed colonization; Erechim Colony; Santa Rosa Colony; First Republic; ACCNPQ::Ciências Humanas::História